Age and Attentional Focus Related Differences in Postural Control - Javad Parhizkar Kohneh Oghaz; Mehdi Zarghami; Ahmad Ghotbi Varzaneh; Amirhosein Ghorbani (University of Tehran, 2013)
Postural control has an important role in daily activities and motor independence. In recent years, conscious aspects of postural control such as attention and cognitive processes have received attention for balance optimization performance. Therefore, the present study designed to examine the age-related differences in postural control in the internal and external focus of attention. For this purpose, displacement of the anterior-posterior, middle-lateral and speed of center of pressure (cop), 22 elderly subjects (mean+SD=59.95±2.12 year) and 22 young men (mean+SD=24.16±2.76 year) who were selected from Shahid Chamran University students and staff purposefully and by availability were measured in three 30-second trials in the internal focus and three 30-second trials in external focus using force platform. After the normality of data had been tested with Kolmogorov-Smirnov test and the equality of variance had been tested using the Levene test, data were analyzed using multivariable variance analysis, one-way variance analysis and MANOVA. Results showed that postural stability of both groups in external focus was more than internal focus. These results supported limited action hypotheses and conscious processes. Also, in both conditions, young group had more postural stability than the elderly. It seems that the weaker performance of the elderly in both external and internal conditions was due to the effects of aging on sensorimotor systems.